Is Elsiella Froeschner, 1981 a valid genus? (Hemiptera: Heteroptera: Pentatomidae: Pentatominae) - Simões, Felipe Lorenz; Ferrari, Augusto; Grazia, Jocélia (Zootaxa, 2012)
The genus Elsiella Froeschner, 1981 is validated based on the analysis of a recently found male specimen of E. plana(Walker, 1867). A cladistic analysis comprising a data set of 40 morphological characters and 22 taxa, including the generaElsiella, Serdia Stål, Similliserdia Fortes & Grazia, Neotibilis Grazia & Barcellos, and Tibilis Stål, was performed. Elsiellaplana is redescribed and illustrated. Maps are provided for Elsiella and Serdia with biogeographical considerations for Serdia.